EFFECT OF PROLONGED STORAGE IN ICE ON NUTRIENTS COMPOSITION AND SENSORY QUALITY OF FRESH POND RAISED CATFISH (Clarias gariepinus Burchell, 1822) (FUDMA JOURNAL OF SCIENCES, 2023)
Fish storage on ice has been one of commonly used methods to preserve fresh fish for subsequent processing and consumption. This study was carried out to assess the effect of prolonged storage in ice on nutrient composition and sensory quality of whole fresh pond raised Catfish (Clarias gariepinus). Live fish samples, with an average weight of 500g were purchased from custom market in Maiduguri Borno state and transported in plastic bucket containing water to the Department of Fisheries, Research and Teaching Farm, University of Maiduguri were the experiment was carried out. The fish were degutted, washed and iced immediately. Data was analyzed using a statistical package SPSS version 20.0. The result of the study shows that that sensory quality of fresh C. gariepinus declines with time when stored in ice and that storage for not more than 15 days could maintain acceptable quality. The nutritional quality of cat fish deteriorated with time when stored in ice. Crude protein decreased from 30% at day1 to 21.57% at day9. Similarly, NFE decrease from 17.78 at day1 to 2.30% at day 15. However, Carcass fat increased with storage time, from 25.25 at day1 to 36.9% at day12. Dry matter content decreased with increasing time of storage indicating increased moisture content of the product.  The result shows that that like any other fish C. gariepinus has a relatively longer shelf life when kept in ice. It is concluded that there is a significant change in the proximate composition of the fish...
Keywords: Storage; Ice; Proximate composition; Sensory quality